Zur medialen Konstruktion des Nationalen Die Schillerfeiern 1859 in Europa und Nordamerika - Logge, Thorsten (Vandenhoeck & Ruprecht Verlag, 2014)
On and around November 10th 1859, hundreds of german-speaking middle-european cities and towns, German exiles and migrants in the United States of America and all over the world, organized partly extensive public celebrations in honor of the German poet Friedrich Schiller. Contemporary witnesses have described the Schiller Centenary as a national festival and it greatly contributed to Friedrich Schiller's status as a national bard and a place of remembrance in Germany.The book discusses the role of the media within the national festival as a major agent in the German nation building process prior to the founding of the Kaiserreich in 1870/71. Depending on the celebrants as communicative producers, the nation herein appears as a media-aided, communicative construction through which the revelers celebrated - and thereby fabricated - the poet Schiller as a national bard and at the same time and most of all miscellaneous valid and locally bound concepts of the German nation
V&R Unipress
Keywords: 1859; 19. Jahrhundert; Deutsches Sprachgebiet; Medienereignis; Nation; Nationalfest; Nationalismus; Nationenbildung; Schillerfeier; Schiller; Friedrich / Jubiläum (1859); Friedrich von